A conceptual study on manpower planning and the importance in organisation - Care Real Jaunis; Roslinah Mahmud (Universiti Malaysia Sabah, 2021)
This paper conceptually reviews the concept of manpower planning and its importance in organizations. Before any organization can work on achieving its goals, the manpower planning takes place first to ensure that every part of the management system is overtaken by the right kinds of people in the right time. The manpower planning process consist of reviewing the organizational goals, analyse current and future needs, develop and implement plan, and finally monitor, evaluate and adjust plan. The study reveals that there is much importance of manpower planning in an organisation. Several evidence from different industries and countries which shown the relationship and benefits of manpower planning implementation has been demonstrated.